Subcellular phenomena in colorectal cancer - Mirams, Gary R. (2008)
The Wnt signalling pathway is involved in stem cell maintenance, differentiation and tissue development, and in so doing plays a key role in controlling the homeostasis of colorectal crypts. In response to an external Wnt stimulus, the intracellular levels of the protein beta-catenin are regulated by the proteins which make up the Wnt signalling pathway. Abnormalities in the Wnt signalling pathway have been implicated in the initiation of colorectal and other cancers.